Comparative studies on the proteins, carbohydrates, acid phosphatase and ribonuclease in caryopses of two orchardgrass (Dactylis glomerata L.) varieties - Eleonora Wieczorek; Anna Bijak; Bronisława Morawiecka (Acta Societatis Botanicorum Poloniae, 2014)
Comparative studies were carried out on some biochemical components in caryopses of two varieties of Dactylis glomerata. The determined protein content depended upon the solvent and amounted to 0.22-0.39 g, with sugar amounting to 2.7-3.6 g and pentoses to 0.30-0.67 g per 100 g of caryopses. The level of pentoses, acid phosphatase and ribonuclease activity was about twice higher in the caryopses of the 'Motycka' variety than that in 'Nakielska'. Similar differences in the two varieties were found in the enzyme activity in the seed and chaff of the Dactylis glomerata caryopses.